The Implementation of EMKM Financial Accounting Standards (SAK) on Tax Compliance - Widyasari, Della; Erdiana, Della (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the effect of the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on the level of tax compliance for MSME actors in Indonesia. The background of this research is based on the low quality of financial reporting and tax non-compliance which are still the main problems in the MSME sector. Using a qualitative approach through the literature study method, this study examines various academic literature, official regulations, and related documents to evaluate the relationship between SAK EMKM-based accounting practices and tax obligations. The results of the study show that the implementation of SAK EMKM can improve the quality of MSME financial statements which has a direct impact on improving the accuracy of tax calculations and reporting. In addition, factors such as accounting literacy, technology support, and the role of supporting institutions also affect the effectiveness of the implementation of this standard. This study concludes that the consistent implementation of SAK EMKM can be a strategic instrument in improving MSME tax compliance, noting that there is synergy between business actors, the government, and other stakeholders